Transformative Learning: the impact of deeper learning approaches in enhancing the transversal competencies (Synergy, 2023)
Dianne Ruffles describes her research, currently underway, that focuses on guided inquiry learning and how this pedagogical approach enhances the transversal competencies, including critical and creative thinking, in young adult learners. Of particular focus is how these approaches can contribute to student achievement and engagement and how as educators, we can better design student experiences.